THE PARADOX OF E-GOVERNANCE! ARE LOCAL AUTHORITIES IN SADC REGION READY? FUMBLING AT A CROSSROADS IN SEARCH OF NEW REALITIES. - Siyavizva, Kudzai Percy; Munuhwa, Shakerod; Mbudaya, Justine (The journal of contemporary issues in business and government, 2022)
The rise of digital platforms cannot be overstated in terms of how it improves the role and functions of local governments in terms of law and order, taxation, legislation, regulation, education, health care, and social development. One of the principal objectives of embracing e-governance is to provide citizens with basic services, enhancing efficiency, transparency, and accountability of local and national governments as well as any other government department or institution. The million-dollar question would be, is Africa ready? Are local authorities ready? If not, what would be the precluding factors in adopting e-governance? This paper seeks to interrogate e-governance practices in the SADC region, exposing how the process has been so dire due to fumbling in the region’s local government institutions. This helps the government to align services with the changing needs of both citizens and other stakeholders as it deliberates the challenges that render the fumbling of local authorities at crossroads. The existing paradox presents a challenge as to the preparedness of local authorities to embrace holistically the dictates of e-governance in a globalised society. An empirical study was conducted to provide primary evidence on e-governance systems in local authorities. The researchers in this paper adopt an in-depth review of the existing body of literature premised on the functions of local authorities in Africa and the SADC region. The findings and recommendations derived from this paper will aid in developing an e- governance model in the SADC region which will feed into ICT policy frameworks. Future research on e-governance across the African continent needs to be commissioned to have a full understanding of e-governance in developing economies.